Principal's Management of Teachers' Performance in the Use of Learning Media - Nita Fajriati; Shaleh Shaleh (Universitas Pakuan, 2025)
Every teacher should have an understanding of learning media, so that learning in class will be more meaningful. The research aims to examine the concept of school principal management in improving teacher performance. This type of research is field study research with qualitative methods. The research was conducted in October – November. The subjects of this study were school principals and madrasahs. Data collection techniques using interviews, documentation and observation. The results of the study are as follows: The principal's management strategy in improving teacher performance in the use of instructional media consists of 3 procedures, namely: 1). Planning Stage: as educators it is necessary to guide teachers to make lesson plans that are adapted to environmental conditions and the needs of students. Preparation of learning plans such as preparation of subject matter, selection of appropriate media according to the lessons and conditions of students, use of learning approaches and methods and assessments carried out at certain times. 2) Organizing stage, namely: changing the plans that have been made into actions assisted by leadership and motivational assistance. 3) Assessment Stage: semicolon, a maximum of 4 words or phrases that are of specific or representative importance for this article.